ECONOMIC TRANSITION IN CHINA AND RUSSIA - Young Choul Kim (European Scientific Journal, ESJ, 2015)
Two of the most profound economic events of the past few decades were the collapse of communism in the Soviet Union and the rapid emergence of the market economy in China. The paths of economic transitions in the two communist countries have been distinct. China’s transition away from state socialism is generally considered a success while Russia’s is not. Why did China have a better transition away from a communist economy than Russia? This study compares and contrasts the evolution of the Chinese and Russian economic reforms over the past few decades. It examines many differences and a few points of similarity. Differences include initial conditions and political leadership as well as external economic environments. Nevertheless, despite Russia’s ongoing economic difficulties, both countries have made substantial progresses in their moves from communism to capitalism. The two countries are currently converging on a similar economic model of state-led development.